a) 2(x-3)=(-6)
x-3=(-6):2
x-3=(-3)
x=(-3)+3
x=0
b) -4(x-2)=12
x-2=12:(-4)
x-2=(-3)
x=(-3)+2
x=(-1)
c) -3(x+1)=(-6)
x+1=(-6):(-3)
x+1=2
x=2-1
x=1
d) -7(x-3)=(-14)
x-3=(-14):(-7)
x-3=2
x=2+3
x=5
e) 2(2x-3)=(-10)
2x-3=(-10):2
2x-3=(-5)
2x=(-5)+3
2x=(-2)
x=(-2):2
x=(-1)
f) 3(2x-3)=(-39)
2x-3=(-39):3
2x-3=(-13)
2x=(-13)+3
2x=(-10)
x=(-10):2
x=(-5)
g) 2(x-8)+4=(-6)
2(x-8)=(-6)-4
2(x-8)=(-10)
x-8=(-10):2
x-8=(-5)
x=(-5)+8
x=3
h) -5(x-3)+7=2
-5(x-3)=2-7
-5(x-3)=(-5)
x-3=(-5):(-5)
x-3=1
x=1+3
x=4
i) -6(x+7)+3x=(-42)
-6x+(-18)+3x=(-42)
-3x=(-42)-(-18)
-3x=(-42)+18
-3x=24
x=24:(-3)
x=(-8)